Spatial−temporal variation of ecological environment quality and driving factors from 2000 to 2020 in Wuliangsu Lake Basin, Northern China - Li, Caixia; Chai, Guoqi; Li, Zhiyuan; Jia, Xiang; Lei, Lingting; Chen, Long; Li, Yunfan; Cao, Yunfeng; Zhu, Ruoning; Mei, Xiaoli; Zhang, Xiaoli (Frontiers in Ecology and Evolution, 2023)
Abstract：Due to global climate change and the intensification of human activities, the ecological function of Wuliangsu Lake Basin has been seriously degraded. Obtaining accurate spatial-temporal dynamics of regional ecological environment quality is essential for the evaluation of ecological management and restoration effects. This study assessed the trend changes and drivers of the Remote Sensing Ecological Index (RSEI) in the Wuliangsu Lake Basin from 2000−2020. Firstly, the trend analysis method and hurst index were used to analyze the temporal and spatial variation of RSEI. Then the main factors of RSEI variation were analyzed using meteorological data, integrated nighttime lighting data, and population density data. Overall, the RSEI shows an increasing trend from the west to the east with a rate of 0.0034 year −1 over the last 21 years. The area change of RSEI was 54.22%,